Highly sensitive fluorescence response of [2.2]paracyclophane modified D−A type chromophores to trace water, pH, acidic gases and formaldehyde. (September 2022) - Ji, Honghan; Duan, Wenzeng; Huo, Yanmin; Liu, Wenjing; Huang, Xianqiang; Wang, Yanlan; Gong, Shuwen
Abstract: Donor (D)−acceptor (A) type compounds have drawn significant attraction recently due to their large Stokes shifted emission and easy-tunable emissive behaviour. Herein, a new family of D−A type [2.2]paracyclophanyl 4 H -pyran-4-one fluorescent molecules (3a −3d ) have been rationally designed and easily synthesized, and they exhibited intensity and wavelength-based fluorescence sensing in response to active hydrogen, polarity, viscosity and acidic/basic vapours. Therefore, visual and quantitative detection of trace water in different organic solvents with low detection limits of 1.39–8.75 ppm were achieved for 3c ; Fluorescence ratiometric detection of pH in the range of 2–7 was achieved for 3b . Moreover, 3a −3d could be served as coated test strips for detecting acidic gases (HCl, TFA, HCOOH and SO2 ) and HCHO with high sensitivity, reversibility, reproducibility and long-time stability. The response times to TFA vapour were 3–5 s, to HCOOH vapour were 5–7 s and to HCHO vapour 32–70 s. These processes could be readily visualized by unaided eye detection under day light and UV-irradiation. Furthermore, the sensing mechanisms were elucidated by X-ray diffraction, NMR and TD-DFT calculations. The present results suggest that the coated test strips of 3a −3d have potential applications in data encryption and decryption and anti-counterfeiting fields. Graphical abstract: Image 1 Highlights: [2.2]Paracyclophane modified D−A type fluorescent molecules were readily synthesized. 3c exhibits visual and quantitative detection of trace water and 3b shows ratiometric detection of pH values. 3a −3d exhibit high sensitivity, reversibility, reproducibility and stability in detecting acidic gases and HCHO.